HUBUNGAN POLA KONSUMSI IKAN DENGAN STATUS GIZI ANAK SEKOLAH DI PESISIR TELUK PANDAN KABUPATEN PESAWERAN - Sutrio, Sutrio; Mulyani, Roza (Universitas Gorontalo, 2020)
School children are important objectives in improving the nutritional status of society. Nutritional status one of them is influenced by protein consumption. Fish is a good source of protein for the growth period and low fish consumption in elementary school students is a problem caused by various factors. This research was to know the pattern of fish consumption with nutritional status in the school children in the Gulf of Pandan Coastal Regency Pesawaran. Research was used cross-sectional research study. The research was conducted at Teluk Pandan Coast Elementary School in August-September 2019. Samples in this study were children of V and VI classes as many as 111 students. Data analysis using chi-square test.The results was showed that the level of protein intake (p = 0.040) was association with the nutritional status while the amount of fish consumption (p = 0.599), the frequency of fish consumption (p = 0.954), the proportion of fish protein consumption (P = 0.076) were not related with nutritional status. The school can utilize media such as posters that contain the importance of consuming fish in school children and include material about the importance of protein intake and fish proteins into physical and sports education subjects and campaigning for the